Outcomes after ORIF of Bicondylar Schatzker VI (AO type C) Tibial Plateau Fractures in an Elderly Population. Issue 6 (June 2022) - Dekhne, Mihir S.; Stenquist, Derek; Suneja, Nishant; Weaver, Michael J.; Petersen, Michael Moerk; Odgaard, Anders; von Keudell, Arvind
Highlights: This study aimed to evaluate age-related outcomes of bicondylar tibial plateau fractures focusing on AO/OTA 41-C or Schatzker VI fractures. We found that elderly patients were more likely to present with lower-energy mechanism of injury and higher comorbidity burden. We found that elderly patients experience poorer total arc motion and report lower PROMIS functional outcome scores after ORIF, though these findings are of uncertain clinical significance. Elderly patients may respond well when treated with ORIF following a tibial plateau fracture. Abstract: Background: The surgical management of bicondylar tibial plateau (BTP) fractures in elderly patients aims to restore knee stability while minimizing soft tissue complications. The purpose of this study was to compare injury characteristics and surgical outcomes after ORIF of BTP fractures (AO/OTA 41-C (Schatzker VI)) in young (< 50 years) versus elderly (> 65 years) patients. Methods: A retrospective cohort study was conducted using data from two American College of Surgeons (ACS) level I trauma centers. Inclusion criteria were: (1) age 18 years or older, (2) bicondylar tibial plateau fracture (AO/OTA 41-C or Schatzker VI), (3) treatment with ORIF, and (4) minimum of 6 months follow-up. Patients between 50 and 65 years of age were excluded. Data collection was performed by reviewing electronic medical records, operative reports, and radiology reports. Results: We identified 323 patients (61% male) with 327 BTP fractures and a median follow-up of 685 days. There were 230 young patients (71%) < 50 years and 93 elderly patients (29%) >6 5 years at time of presentation. Elderly patients were significantly more likely to have a low energy mechanism of injury (44.6 vs. 16.2%, p < 0.001), and present with diabetes (19.4 vs. 4.4%, p < 0.001) or coronary artery disease (12.9 vs. 1.3%, p < 0.001). Elderly patients were also significantly less likely to undergo staged management with initial knee-spanning external fixation followed by delayed ORIF (19.2 vs. 33.9%, p  = 0.008). Elderly patients had a lower arc of motion at final follow-up (105 vs. 113°, p < 0.001) and reduced PROMIS-10 function scores (43.8 vs. 49.8, p  = 0.013). No differences were observed in rates of superficial infection, deep infection, reoperation, or EQ-5D scores between age groups. Conclusions: This is the largest study to compare injury characteristics and outcomes after ORIF of BTP fractures according to age. Elderly patients (age > 65 years) sustained BTP fractures by lower energy mechanisms than their younger counterparts with similar fracture patterns and were often managed with ORIF. The results of this study suggest that ORIF of BTP fractures in elderly patients is associated with similar complication rates and outcomes as in younger patients despite higher comorbidities and poorer bone quality in the elderly population.